Metastatic colorectal carcinoma with signet-ring cells: Clinical, histological and molecular description from an Association des Gastro-Entérologues Oncologues (AGEO) French multicenter retrospective cohort. Issue 3 (March 2022) - Allart, Marion; Leroy, Florence; Kim, Stephano; Sefrioui, David; Nayeri, Mihane; Zaanan, Aziz; Rousseau, Benoit; Ben Abdelghani, Meher; de la Fouchardière, Christelle; Cacheux, Wulfran; Legros, Romain; Louafi, Samy; et al.
Abstract: Background: Metastatic signet-ring cell colorectal carcinoma is rare. We analyzed its clinicopathological and molecular features, prognostic factors and chemosensitivity. Methods: Retrospective study from 2003 to 2017 in 31 French centers, divided into three groups: curative care (G1), chemotherapy alone (G2), and best supportive care (G3). Results: Tumors were most frequently in the proximal colon (46%), T4 (71%), and poorly differentiated (86%). The predominant metastatic site was peritoneum (69%). Microsatellite instability and BRAF mutation were found in 19% and 9% (mainly right-sided) of patients and RAS mutations in 23%. Median overall survival (mOS) of the patients ( n  = 204) was 10.1 months (95%CI: 7.9;12.8), 45.1 for G1 ( n  = 38), 10.9 for G2 ( n  = 112), and 1.8 months for G3 ( n  = 54). No difference in mOS was found when comparing tumor locations, percentage of signet-ring cell contingent and microsatellite status. In G1, relapse-free survival was 14 months (95%CI: 6.5–20.9). In G2, median progression-free survival (PFS) was 4.7 months (95%CI: 3.6;5.9]) with first-line treatment. Median PFS was higher with biological agents than without (5.0 vs 3.9 months, p  = 0.016). Conclusions: mSRCC has a poor prognosis with specific location and molecular alterations resulting in low chemosensitivity. Routine microsatellite analysis should be performed because of frequent MSI-high tumors in this population.